Helicobacter Pylori Infection and Brain Dysfunction - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Helicobacter pylori infection was identified in 5 children with severe neurologic impairment who underwent upper gi endoscopy at the Alfred I duPont Institute, Wilmington, De, and Jefferson Medical College, Philadelphia.